2021
DOI: 10.1016/j.csbj.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

De novo genome assembly of the potent medicinal plant Rehmannia glutinosa using nanopore technology

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 100 publications
0
36
0
Order By: Relevance
“…These transcripts in plants may contain protein coding sequences, isoforms, and non-coding RNAs [ 21 , 22 , 24 ]. A reference genome for R. glutinosa has recently been reported and is predicted to contain 48,475 protein-coding genes [ 25 ]. The number of predicted genes differs from the 58,949 predicted CDS in our study ( Table 1 ), possibly because our transcriptome data also contain the isoforms of genes generated by alternative splicing [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These transcripts in plants may contain protein coding sequences, isoforms, and non-coding RNAs [ 21 , 22 , 24 ]. A reference genome for R. glutinosa has recently been reported and is predicted to contain 48,475 protein-coding genes [ 25 ]. The number of predicted genes differs from the 58,949 predicted CDS in our study ( Table 1 ), possibly because our transcriptome data also contain the isoforms of genes generated by alternative splicing [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, four orobanchaceous species’ genomes have been released, the autotrophic Rehmannia glutinosa (19) and the obligate hemiparasite Striga asiatica (15) and facultative hemiparasite Phtheirospermum japonicum (20) and Pedicularis cranolopha (21), but the genomes of orobanchaceous holoparasites are still lacking. In this study, we sequenced and assembled high-quality genomes of the autotroph Lindenbergia luchunensis and the holoparasites Orobanche cumana and Phelipanche aegyptiaca , among which the latter two are notorious parasitic pests in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of gene loss is generally considered to be positively associated with the degree of parasitism (16), as a greater degree of parasitism requires higher dependency on the host and fewer physiological processes are needed by the parasite itself, and gene loss may enable the parasite to synchronize its own physiology with that of the host, probably resulting in better fitness (18). Thus far, four orobanchaceous species' genomes have been released, the autotrophic Rehmannia glutinosa (19) and the obligate hemiparasite Striga asiatica (15) and facultative hemiparasite Phtheirospermum japonicum (20) and Pedicularis cranolopha (21), but the genomes of orobanchaceous holoparasites are still lacking. In this study, we sequenced and assembled high-quality genomes of the autotroph Lindenbergia luchunensis and the holoparasites Orobanche cumana and Phelipanche aegyptiaca, among which the latter two are notorious parasitic pests in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study confirmed that most prenyltransferases involved in terpenoid backbone biosynthesis were the member of FPP/GGPP synthase families, and all prenyltransferases were interacted with biotin carboxylase CAC2 (Chen et al, 2021 ). A reference genome of R. glutinosa was reported using Nanopore technology, Illumina, and Hi-C sequencing, in which the expansion of the UDP-dependent glycosyltransferases and the terpene synthase gene families was demonstrated (Ma et al, 2021 ). Nevertheless, the regulation of genes involved in iridoid glycoside biosynthesis was rarely reported in R. glutinosa .…”
Section: Discussionmentioning
confidence: 99%